Complete mitochondrial genome assembly and comparison of Camellia sinensis var. Assamica cv. Duntsa - Li, Jin; Tang, Han; Luo, Hua; Tang, Jun; Zhong, Ni; Xiao, Lizheng (Frontiers in Plant Science, 2023)
Camellia sinensis var. Assamica cv. Duntsa (C.duntsa), a valuable Theaceae from Hunan Province, has been looked at as a precious tea resource by local farmers because of its economic and ecological value. Genomics study on C.duntsa is essential for the domestication and enhancement of tea tree varieties. In the current study, we used a hybrid approach based on Illumina and PacBio data to sequence and assemble the mitochondrial genome of C.duntsa.The mitochondrial genome of C.duntsa was estimated to be 1,081,996 base pairs (bp) and eighty-one genes consisting of one pseudogene, three ribosomal RNA (rRNA) genes, thirty transfer RNA (tRNA) genes, and forty-seven protein-coding genes (PCGs). Tetramer repetitions made up 43.90% of simple sequence repeats (SSRs). The codon usage bias of the Theaceae mitochondrial gene atp9 was altered by mutation, but the codon usage of other genes was shaped by natural selection. Besides, there are eighteen gene-containing homologous regions between the chloroplast and mitochondrial genomes of C. duntsa.Some genomes including atp8, cox1, cox3, nad7, nad9, rpl16, rpl2, rps19, rps4, and sdh4 are absent in the mitochondrial genome of several Theaceae plant.However, C. duntsa maintains these genes integrity and functionality. Another gene, rps16, is either lacking from the mitochondrial genome of C. duntsa or is present as a pseudogene. C. duntsa and C. sinensis (OM809792) are very similar, as shown by a collinear match across four species of Theaceae; the most conservative genes are nad5, atp9, cox2, rps3, trnA-TGC, trnI-GAT, rrn18, trnV-GAC, and ccmFN. Similarly, the genome's phylogenetic trees revealed that C. duntsa was the sister species to C. sinensis. The results confirmed that the C. duntsa and C. sinensis (OM809792) mitochondrial genome underwent gene rearrangement.In general, our results shows that genomic information from organelles can help us understand plant phylogeny and can also be used to make molecular markers and study how genetic traits change over time. Our research will contribute to the population genetics and evolution of Theaceae.